Expression profile of miRNAs in urine samples of bladder cancer patients. (3rd December 2018) - Nekoohesh, Leila; Modarressi, Mohammad Hossein; Mowla, Seyed Javad; Sadroddiny, Esmaeil; Etemadian, Masoud; Afsharpad, Mandana; Zolfaghari, Faezeh; Barzegari, Manijeh; Saffari, Mojtaba; Oskooei, Vahid Kholghi; Motevaseli, Elahe; Ghafouri-Fard, Soudeh
Aim: miRNAs have been suggested as biomarkers for bladder cancer. We aimed to find a diagnostic panel of miRNAs based on differential expression of miRNAs in urine specimens of patient with bladder cancer compared with control group.Methods: miR-141, miR-10b, miR-34b and miR-103 were selected to assess their expression in urine samples of 66 bladder cancer patients and 53 matched controls using quantitative real time PCR.Results: miR-10b and miR-34b were upregulated in cases compared with controls. The combination of four miRNAs showed a sensitivity of 75% and specificity of 63.5% with a diagnostic power of 72%.Conclusion: Certain miRNAs can be used as biomarkers for early diagnosis of bladder cancer.